The unionization process of police unions in Uruguay - Sabrina Calandrón; Santiago Galar; Mariana Da Silva Lorenz (Íconos)
The National Police of Uruguay obtained the right to unionize in 2006. This right was obtained after an intense intervention process of the Police in the public arena. With the regional context considered, this article seeks to analyze the unionization dimensions of the Uruguayan Police, paying close attention to the political tools developed and the diverse union affiliation in this process. Among its key results, this research highlights how the union model, which has been created by political sectors and is very different from the “trade union”, makes the fragmentation and diversification of organizations possible. These organizations coexist, associate with each other, and contest power according to the circumstances and the political opportunities present with the incumbent government. This research was conducted with a qualitative and exploratory methodology due to the lack of previous studies on this topic. In-depth interviews with key informants were conducted, and the information from two newspapers (2015-2018 period) made it possible to reconstruct facts and to give voices to important actors. Finally, institutional websites from unions were registered, which were complimented with information about laws and decrees related to the themes of analysis of the corpus.